The effects of sildenafil on rectal sensitivity and tone in patients with the irritable bowel syndrome - Goncalves de Medeiros, M. T.; de Oliveira, R. B. [UNESP]; dos Santos, A. A.; de Leopoldino, D. M.; Oliveira Lima, M. C.; Arrais Nobre, R.; Nobre e Souza, M. A. (Wiley-Blackwell, 2012)
BackgroundVisceral tone supposedly affects gut sensitivity in irritable bowel syndrome (IBS). Sildenafil increases nitric oxide and influences visceral compliance.AimTo evaluate the effects of sildenafil tone inhibition on rectal sensitivity.MethodsEight controls and 21 IBS patients (Rome II) were enrolled in a double-blind study, after dosing with placebo or sildenafil (50 mg p.o.). Thresholds for first sensation, first desire to defecate, pain and supraliminar pain were the sensory endpoints, measured with a barostat and 600-mL rectal bag. Pain (100-mm VAS) and depression-anxiety (Hamilton questionnaire) were scored.ResultsIrritable bowel syndrome rectal compliance and sensory-endpoint thresholds were similar to controls. Five IBS patients had pain threshold lower than controls 95% confidence interval (hypersensitive). Depression score was greater in IBS than controls (11.9 +/- 1.3 vs. 6.3 +/- 2.5, P = 0.036). In IBS, pain intensity was nonsignificantly higher (37.6 +/- 5.3 mm vs. 23.4 +/- 8.5 mm, P = 0.064) and supraliminar pain intensity was greater (45.6 +/- 5.4 mm vs. 25.9 +/- 5.1 mm, P = 0.044) than controls. IBS rectal relaxation increased volume (155.4 +/- 41.3 mL vs. 118.8 +/- 47.7 mL, P = 0.004) and tension (193.1 +/- 118.6 mmHg mL(-1) vs. 133.2 +/- 98.1 mmHg mL(-1), P = 0.019) for triggering first desire to defecate but not for other perceptions. Sildenafil increased volume for both first desire to defecate and pain in the hypersensitive IBS patients. Sildenafil increased rectal compliance only in diarrhoea-IBS. Mixed-IBS obtained higher anxiety (12.9 +/- 1.3 vs. 5.9 +/- 3.1, P < 0.05) and depression scores (13.9 +/- 1.9 vs. 6.3 +/- 2.5, P < 0.05) and reported more intense supraliminar pain (53.6 +/- 9.8 mm vs. 25.9 +/- 5.1 mm, P < 0.05) than controls.ConclusionsRectal relaxation following dosing with sildenafil 50 mg increased the first desire to defecate threshold in IBS as a whole, but decreased pain only in the hypersensitive subset. Mixed-IBS presented higher supraliminar pain and anxiety-depression scores.